A drag reducing agent and a method for preparing the same
Patent Information
- Application Number
- CN202611024207.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-10
- Publication Date
- 2026-10-23
AI Technical Summary
[0003]常见的油品减阻剂主要作用成分是α-烯烃长链聚合物,此类分子在管道高速流体剪切环境下极易断链分解而逐渐失去减阻性能,不断补充减阻剂维持管输的减阻效果会导致输送成本的提高
本发明减阻剂制备中,同时增加引入乙二醇和铝掺杂氧化锌;纳米铝掺杂氧化锌表面存在大量不饱和金属氧位点,优先吸附体系中游离乙二醇分子,形成一层无机缓冲包覆层,阻止乙二醇直接接触硅烷改性二氧化硅并与KH550氨基结合,有效削弱/抵消引入乙二醇所带来的负面影响。
Smart Images

Figure CN122960842A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of drag-reducing agent technology, specifically relating to a drag-reducing agent and its preparation method. Background Technology
[0002] Drag reducers are mainly used in fluid transportation systems, such as those for crude oil, refined oil, sewage, slurry, water supply and drainage, and fire-fighting water. Their core principle is to suppress fluid turbulence and eddies, reduce energy loss, and lower pipeline friction resistance. Oil drag reducers are chemical additives that, when injected in small amounts into pipelines transporting refined oil or crude oil, can significantly reduce pipeline friction and increase pipeline throughput.
[0003] Common oil drag-reducing agents primarily consist of α-olefin long-chain polymers. These molecules are prone to chain breakage and decomposition under the high-speed fluid shear environment of pipelines, gradually losing their drag-reducing properties. Continuously replenishing drag-reducing agents to maintain the drag-reducing effect leads to increased transportation costs. To address this issue, existing technologies use the silane coupling agent KH550 to modify the surface of nano-SiO2, obtaining silane-modified silica. This allows for better interaction with polyα-olefins to form nanocomposite drag-reducing agents, which exhibit superior drag-reducing performance. Further improving the drag-reducing capacity of these agents remains a topic worthy of continued research. Summary of the Invention
[0004] To address the problems existing in the background art, the present invention provides a drag-reducing agent and its preparation method, which further improves the drag-reducing ability of the prepared drag-reducing agent based on the use of silane-modified silicon dioxide.
[0005] To achieve the above objectives, in a first aspect, the present invention provides a method for preparing a drag-reducing agent, comprising the following steps: S1. By weight, add 2.0-2.2 parts of silane-modified silica to 85-87 parts of polyalphaolefin drag reducer slurry, then add 10-12 parts of compatibilizer, stir, and obtain the basic mixture. S2. Add 0.21-0.23 parts of aluminum-doped zinc oxide and 0.32-0.35 parts of ethylene glycol to the basic mixture obtained in S1, and stir at 55-65 rpm for 6-7 hours at 50±1℃ to obtain the drag-reducing agent.
[0006] Furthermore, the preparation method of the silane-modified silica is as follows: A1. Disperse 100g of nano-silica in 800-850mL of 95% ethanol aqueous solution and sonicate for 10min to obtain nano-silica solution; disperse 15g of silane coupling agent KH550 in 150-170mL of 95% ethanol aqueous solution to obtain coupling agent solution. A2. Adjust the pH of the coupling agent solution obtained in A1 to 3-4 with dilute hydrochloric acid, and hydrolyze it at a certain temperature for 1.5-2 hours. Then mix it with the nano silica solution obtained in A1, react it with ultrasound, and then dry, wash, and dry it a second time to obtain the final product.
[0007] Furthermore, in A2, the specific procedure for the ultrasonic reaction is as follows: ultrasonic reaction at 50℃ for 4-5 hours.
[0008] Furthermore, in A2, the specific operations for drying, cleaning, and secondary drying are as follows: drying at 40℃ under normal pressure for 4 hours, and vacuum drying at 80℃ for 24 hours; cleaning with 95% ethanol aqueous solution 5 times; and vacuum drying at 80℃ for 24 hours.
[0009] Furthermore, the method for preparing the aluminum-doped zinc oxide is as follows: B1. Dissolve 0.02 mol zinc acetate dihydrate in 50 mL of a mixture of ethylene glycol methyl ether and anhydrous ethanol, add 0.02 mol stabilizer ethanolamine (MEA) and 0.27 g formamide to obtain solution one; B2. Dissolve 0.395g of aluminum nitrate nonahydrate in 50mL of anhydrous ethanol to obtain solution two; B3. Add the solution obtained from B2 to the solution obtained from B1, stir, and a uniform transparent sol will be formed. Anneal the solution to obtain the final product.
[0010] Furthermore, in B3, the specific stirring operation is as follows: stir at 60℃ for 2-2.5 hours.
[0011] Furthermore, in B3, the specific annealing procedure is as follows: anneal at 530℃ for 4-4.5 hours.
[0012] Furthermore, the compatibilizer is prepared as follows: C1. Add 20g of poly-α-olefin to 700g of anhydrous ethanol and disperse completely. Use an ultrasonic cell disruptor to sonicate for 30-40 minutes. Add 3g of maleic anhydride and continue sonicating for 10-30 minutes to obtain anhydride-grafted poly-α-olefin. C2. Pour the anhydride-grafted poly-α-olefin obtained in C1 into toluene, heat under reflux for 2.8-3.0 h, then pour the solution into acetone and filter. Recover the insoluble substances, wash with acetone, and dry to obtain the final product.
[0013] Secondly, the present invention provides a drag-reducing agent prepared by the above-described preparation method.
[0014] This application has the following beneficial effects: In the preparation of the drag-reducing agent of this invention, ethylene glycol and aluminum-doped zinc oxide are introduced simultaneously. The surface of nano-aluminum-doped zinc oxide has a large number of unsaturated metal oxygen sites, which preferentially adsorb free ethylene glycol molecules in the system to form an inorganic buffer coating layer, preventing ethylene glycol from directly contacting silane-modified silica and binding with KH550 amino groups, effectively weakening / counteracting the negative effects of introducing ethylene glycol.
[0015] Furthermore, ethylene glycol assists in the uniform dispersion of aluminum-doped zinc oxide to construct a multi-layered shear-resistant network; the residual hydroxyl groups of ethylene glycol can wet the aluminum-doped zinc oxide powder, reducing the surface energy of the aluminum-doped zinc oxide particles and preventing their aggregation; the uniformly dispersed aluminum-doped zinc oxide and silane-modified silica can better form a dual-inorganic nano-synergistic reinforcement system; during turbulent shearing, the two jointly anchor the polymer chains, share the fluid shear stress, and significantly inhibit polymer chain breakage; at the same time, the antioxidant capacity of aluminum-doped zinc oxide is fully utilized; thus, the drag reduction capability is synergistically improved. Attached Figure Description
[0016] Figure 1 This is a comparative trend chart showing the drag reduction performance test results of the drag reduction agent samples prepared in Example 1 and Comparative Examples 1-3 of the present invention. Detailed Implementation
[0017] The present application will be further described in detail below with reference to the embodiments.
[0018] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of this application are all commercially available.
[0019] (I) The preparation method of silane-modified silica involved in the embodiments / comparative examples of this invention is as follows: A1. Take 100g of nano-silica (particle size 50±10nm, purity ≥99.8%, specific surface area 200±30m²) 2 / g, commercially available analytical grade, vacuum dried at 120℃ for 24h to remove adsorbed moisture before use) was dispersed in 820mL of 95% ethanol aqueous solution and ultrasonically dispersed for 10min to obtain nano silica solution. 15g of silane coupling agent KH550 (γ-aminopropyltriethoxysilane, purity ≥97%) was dispersed in 160mL of 95% ethanol aqueous solution to obtain the coupling agent solution.
[0020] A2. Adjust the pH of the coupling agent solution obtained in A1 to 3.6 with dilute hydrochloric acid (prepared by diluting 37% concentrated hydrochloric acid with deionized water, concentration 1.0 mol / L). Maintain a water bath temperature of 25±1℃ and carry out the hydrolysis reaction (stir with a glass rod every 30 minutes for 30 seconds each time to ensure uniform hydrolysis). After hydrolysis for 1.8 hours, mix with the nano-silica solution obtained in A1. Stir at 600W power and 40kHz frequency, maintaining a stirring speed of 300r / min. After ultrasonic reaction at 50℃ for 4.5 hours, dry at 40℃ under normal pressure for 4 hours, and then dry under vacuum (vacuum degree ≤100Pa) at 80℃ for 24 hours. Wash five times with 95% ethanol aqueous solution and dry under vacuum at 80℃ for 24 hours to obtain the final product.
[0021] (II) The preparation method of aluminum-doped zinc oxide involved in the embodiments / comparative examples of the present invention is as follows: B1. Dissolve 0.02 mol zinc acetate dihydrate in 50 mL of a mixture of ethylene glycol methyl ether and anhydrous ethanol (volume ratio 1:1), place the solution in a constant temperature magnetic stirring water bath, set the temperature to 25℃ and the stirring speed to 500 r / min, and stir for 15 min; then add 0.02 mol stabilizer ethanolamine (MEA) and 0.27 g formamide, and continue stirring at 25℃ and 500 r / min for 10 min to ensure that all components are fully dissolved, to obtain solution one.
[0022] Zinc acetate dihydrate, analytical grade, purity ≥99.0%, is a white crystalline powder used to provide the zinc source. Ethylene glycol methyl ether, analytical grade, purity ≥99.5%, is a colorless, transparent liquid and serves as the main solvent, mixed with anhydrous ethanol at a 1:1 volume ratio to form a mixed solvent system. Anhydrous ethanol, analytical grade, purity ≥99.7%, is a colorless liquid and serves as an auxiliary solvent, both dissolving and regulating the system's viscosity. Ethanolamine (MEA), analytical grade, purity ≥99.0%, is a colorless, viscous liquid and serves as a stabilizer to ensure sol stability. Formamide, analytical grade, purity ≥99.5%, is a colorless, transparent liquid and serves as an auxiliary complexing agent to improve sol uniformity.
[0023] B2. Dissolve 0.395g of aluminum nitrate nonahydrate in 50mL of anhydrous ethanol, place the solution in a constant temperature magnetic stirring water bath, set the temperature to 25℃ and the stirring speed to 400r / min, stir for 20min until the aluminum nitrate nonahydrate is completely dissolved, and obtain solution two.
[0024] Aluminum nitrate nonahydrate is of analytical grade with a purity of ≥99.0%, and is a colorless crystal used to provide an aluminum doping source.
[0025] B3. Add the solution obtained from B2 to the solution obtained from B1. Stir in a constant temperature magnetic stirring water bath at 60°C and 600 r / min for 2.3 h to form a uniform and transparent sol. First, place it in a forced-air drying oven and dry at 80°C for 12 h to remove most of the organic solvent. Then, place it in a muffle furnace and heat it at a rate of 5°C / min to 530°C. Hold it at this temperature for annealing for 4.2 h. After annealing, allow it to cool naturally to room temperature to obtain the final product.
[0026] (III) The preparation method of the compatibilizer involved in the embodiments / comparative examples of the present invention is as follows: C1. Add 20g of poly-α-olefin to 700g of anhydrous ethanol and disperse completely. Use an ultrasonic cell disruptor to sonicate for 35min at an ultrasonic power of 600W and an ultrasonic frequency of 25kHz. Then add 3g of maleic anhydride and continue to sonicate for 20min to obtain anhydride-grafted poly-α-olefin.
[0027] C2. Slowly pour the anhydride-grafted poly-α-olefin obtained in C1 into a 1000 mL round-bottom flask, then pour it into 300 mL of toluene (rinse the inner wall of the beaker three times to ensure that all residual product is transferred to the round-bottom flask). Heat under reflux for 3.0 h, then allow it to cool naturally to 50 °C. Slowly pour the solution from the round-bottom flask into a 1000 mL beaker containing 800.0 mL of acetone while stirring with a glass rod to allow the grafted product to fully precipitate. Let it stand for 30 min to allow the precipitate to settle completely. Use a circulating water vacuum pump for filtration, recover the insoluble matter obtained by filtration, wash with acetone, and dry to obtain the final product.
[0028] (iv) Other specific details of the embodiments / comparative examples of the present invention are as follows.
[0029] Example 1 A method for preparing a drag-reducing agent includes the following steps: S1. By weight, add 2.1 parts of silane-modified silica to 86 parts of polyalphaolefin drag reducer slurry (commercially available), then add 11 parts of compatibilizer, stir, and obtain the basic mixture.
[0030] S2. Add 0.22 parts of aluminum-doped zinc oxide and 0.33 parts of ethylene glycol to the basic mixture obtained in S1, and stir at 60 rpm for 6.5 h at 50 °C to obtain the drag-reducing agent.
[0031] Example 2 A method for preparing a drag-reducing agent includes the following steps: S1. By weight, add 2.0-2.2 parts of silane-modified silica to 85-87 parts of polyalphaolefin drag reducer slurry, then add 10-12 parts of compatibilizer, stir, and obtain the basic mixture.
[0032] S2. Add 0.21-0.23 parts of aluminum-doped zinc oxide and 0.32-0.35 parts of ethylene glycol to the basic mixture obtained in S1, and stir at 60 rpm for 6.5 h at 50 °C to obtain the drag-reducing agent.
[0033] Example 3 A method for preparing a drag-reducing agent includes the following steps: S1. By weight, add 2.0-2.2 parts of silane-modified silica to 85-87 parts of polyalphaolefin drag reducer slurry, then add 10-12 parts of compatibilizer, stir, and obtain the basic mixture.
[0034] S2. Add 0.21-0.23 parts of aluminum-doped zinc oxide and 0.32-0.35 parts of ethylene glycol to the basic mixture obtained in S1, and stir at 60 rpm for 6.5 h at 50 °C to obtain the drag-reducing agent.
[0035] Comparative Example 1 The difference between this comparative example and Example 1 is that aluminum-doped zinc oxide and ethylene glycol are not added; specifically, a method for preparing a drag-reducing agent includes the following steps: S1. By weight, add 2.1 parts of silane-modified silica and 11 parts of compatibilizer to 86 parts of polyalphaolefin drag reducer slurry, stir, and obtain the basic mixture.
[0036] S2. Stir the base mixture obtained in S1 at 50°C at 60 rpm for 6.5 h to obtain the drag reducer.
[0037] Comparative Example 2 The difference between this comparative example and Example 1 is that aluminum-doped zinc oxide is not added; specifically, a method for preparing a drag-reducing agent includes the following steps: S1. By weight, add 2.1 parts of silane-modified silica and 11 parts of compatibilizer to 86 parts of polyalphaolefin drag reducer slurry, stir, and obtain the basic mixture.
[0038] S2. Add 0.33 parts of ethylene glycol to the basic mixture obtained in S1, and stir at 60 rpm for 6.5 h at 50 °C to obtain the drag reducer.
[0039] Comparative Example 3 The difference between this comparative example and Example 1 is that ethylene glycol is not added; specifically, a method for preparing a drag-reducing agent includes the following steps: S1. By weight, add 2.1 parts of silane-modified silica and 11 parts of compatibilizer to 86 parts of polyalphaolefin drag reducer slurry, stir, and obtain the basic mixture.
[0040] S2. Add 0.22 parts of aluminum-doped zinc oxide to the basic mixture obtained in S1, and stir at 60 rpm for 6.5 h at 50 °C to obtain the drag-reducing agent.
[0041] Test Example: Test Subjects: Drag-reducing agent samples prepared in Examples 1-3 and Comparative Examples 1-3.
[0042] Experimental Items and Methods: Rotating Disc Method for Drag Reduction Rate Testing: An indoor rotating disc apparatus was used with diesel fuel as the fluid. The torque variation during the experiment was investigated at 25℃ with a drag-reducing agent concentration of 50 mg / L, and the drag reduction rate of the corresponding test sample was calculated. The stainless steel disc was 13 cm in diameter and 0.3 cm thick. A covered circular container, made of stainless steel, had an inner diameter of 17 cm and an inner height of 7.5 cm. The entire container was placed in a temperature-controlled water bath. A PLC circuit was used to adjust the motor speed (0–3000 rpm). The motor transmitted power to the disc via a coupling. A torque sensor (range 0–5 N·m, accuracy 0.0001 N·m) was installed between the motor and the disc shaft to measure and collect the drag torque generated by the disc during rotation (Ts is the drag torque of 0# diesel fuel at 25℃). p (This refers to the drag torque after adding the drag-reducing agent), and then the drag reduction ratio D is calculated. R :D R =(Ts-T p ) / Ts×100%.
[0043] Experimental results: see Table 1.
[0044] Table 1. Experimental Data Results Analysis: Combining the data in Table 1 and... Figure 1 The results of the analysis of Example 1 and Comparative Examples 1-3 were as follows: Specifically, a comparison was made between Comparative Example 1 and Comparative Example 2. It was found that, compared to Comparative Example 1, the addition of ethylene glycol alone in Comparative Example 2 resulted in a decrease in the drag-reducing performance of the prepared drag-reducing agent. This is mainly because, when ethylene glycol is introduced alone, it is a highly polar diol with a large number of hydroxyl groups in its molecule. These hydroxyl groups can combine with the amino groups of KH550, blocking the interaction between KH550 and the polyalphaolefin matrix. This weakens the supporting and reinforcing effect of silane-modified silica on the polymer chain, leading to easy breakage of long chains under transport shear and a decrease in drag-reducing ability.
[0045] Specifically, comparing Comparative Examples 1 and 3, it can be seen that, compared to Comparative Example 1, the addition of aluminum-doped zinc oxide alone in Comparative Example 3 resulted in improved drag-reducing performance of the prepared drag-reducing agent. Furthermore, comparing with Example 1, it can be seen that the simultaneous introduction of ethylene glycol and aluminum-doped zinc oxide produces a synergistic effect, jointly improving the drag-reducing performance of the prepared drag-reducing agent.
[0046] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.
[0047] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.
Claims
1. A method for preparing a drag-reducing agent, characterized in that, Includes the following steps: S1. By weight, add 2.0-2.2 parts of silane-modified silica to 85-87 parts of polyalphaolefin drag reducer slurry, then add 10-12 parts of compatibilizer, stir, and obtain the basic mixture. S2. Add 0.21-0.23 parts of aluminum-doped zinc oxide and 0.32-0.35 parts of ethylene glycol to the basic mixture obtained in S1, and stir at 55-65 rpm for 6-7 hours at 50±1℃ to obtain the drag-reducing agent.
2. The method for preparing the drag-reducing agent according to claim 1, characterized in that, The preparation method of the silane-modified silica is as follows: A1. Disperse 100g of nano-silica in 800-850mL of 95% ethanol aqueous solution and sonicate for 10min to obtain nano-silica solution; disperse 15g of silane coupling agent KH550 in 150-170mL of 95% ethanol aqueous solution to obtain coupling agent solution. A2. Adjust the pH of the coupling agent solution obtained in A1 to 3-4 with dilute hydrochloric acid, and hydrolyze it at a certain temperature for 1.5-2 hours. Then mix it with the nano silica solution obtained in A1, react it with ultrasound, and then dry, wash, and dry it a second time to obtain the final product.
3. The method for preparing the drag-reducing agent according to claim 2, characterized in that, In A2, the specific procedure for the ultrasonic reaction is as follows: ultrasonic reaction at 50℃ for 4-5 hours.
4. The method for preparing the drag-reducing agent according to claim 2, characterized in that, In A2, the specific operations for drying, cleaning, and secondary drying are as follows: dry at 40℃ under normal pressure for 4 hours, and vacuum dry at 80℃ for 24 hours; wash with 95% ethanol aqueous solution 5 times; and vacuum dry at 80℃ for 24 hours.
5. The method for preparing the drag-reducing agent according to claim 1, characterized in that, The method for preparing the aluminum-doped zinc oxide is as follows: B1. Dissolve 0.02 mol zinc acetate dihydrate in 50 mL of a mixture of ethylene glycol methyl ether and anhydrous ethanol, add 0.02 mol stabilizer ethanolamine (MEA) and 0.27 g formamide to obtain solution one; B2. Dissolve 0.395g of aluminum nitrate nonahydrate in 50mL of anhydrous ethanol to obtain solution two; B3. Add the solution obtained from B2 to the solution obtained from B1, stir, and a uniform transparent sol will be formed. Anneal the solution to obtain the final product.
6. The method for preparing the drag-reducing agent according to claim 5, characterized in that, In B3, the specific stirring procedure is as follows: stir at 60℃ for 2-2.5 hours.
7. The method for preparing the drag-reducing agent according to claim 5, characterized in that, In B3, the specific annealing procedure is as follows: anneal at 530℃ for 4-4.5 hours.
8. The method for preparing the drag-reducing agent according to claim 1, characterized in that, The compatibilizer is prepared as follows: C1. Add 20g of poly-α-olefin to 700g of anhydrous ethanol and disperse completely. Use an ultrasonic cell disruptor to sonicate for 30-40 minutes. Add 3g of maleic anhydride and continue sonicating for 10-30 minutes to obtain anhydride-grafted poly-α-olefin. C2. Pour the anhydride-grafted poly-α-olefin obtained in C1 into toluene, heat under reflux for 2.8-3.0 h, then pour the solution into acetone and filter. Recover the insoluble substances, wash with acetone, and dry to obtain the final product.
9. A drag-reducing agent, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 8.
